1980
DOI: 10.1002/j.0022-0337.1980.44.9.tb01398.x
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of two methods for evaluating primary class II cavity preparations

Abstract: An analytical system for evaluating class II cavity preparations in primary teeth was developed and tested and then compared with the traditional global (glance and grade) evaluation method with respect to intraexaminer and interexaminer reliability. Fifteen examiners with varied experience in clinical evaluation rated 24 class II cavity preparations in ivorine inverted question mark primary teeth mounted in dentoforms inverted question mark in a simulated clinical setting. The global method of scoring was com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
12
0

Year Published

1987
1987
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 0 publications
2
12
0
Order By: Relevance
“…The only significant differences between the studies were the numbers of teeth examined and the choice of crown preparation. In the context of other dental laboratory studies, a large variation in inter‐examiner agreement has been reported (0.012—0.94), and the results of this study fall within this range Although the kappa statistics in this study are low, the agreement between peer assessment and assessor scores is similar to inter‐examiner agreement. This finding is also in keeping with other studies investigating peer assessment that have found similar results when using both methods .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The only significant differences between the studies were the numbers of teeth examined and the choice of crown preparation. In the context of other dental laboratory studies, a large variation in inter‐examiner agreement has been reported (0.012—0.94), and the results of this study fall within this range Although the kappa statistics in this study are low, the agreement between peer assessment and assessor scores is similar to inter‐examiner agreement. This finding is also in keeping with other studies investigating peer assessment that have found similar results when using both methods .…”
Section: Discussionmentioning
confidence: 99%
“…Problems of subjectivity associated with assessment have been recognised for several decades, not only in Dentistry, but across other academic disciplines. Multiple studies have shown significant inter‐examiner variability when assessing dental operative skills, whilst intra‐examiner variability appears to be less of a problem . Reasons suggested for this variability have included reluctance to award good grades if the preparation had been carried out by a student .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For the two examiners, this agreement may be considered highly acceptable, because it exceeded 90%. Similarly, Goepferd and Kerber ( 8 ) used the analytical system for evaluation using specific standards. They reported that the method was superior to the glance and grade method in reducing the variability among the two examiners.…”
Section: Discussionmentioning
confidence: 99%
“…Investigators in more recent years have concentrated on the development of marking systems centered on specific criteria and checklists as an alternative to the glance and grade method commonly used in clinical sessions, in order to improve rater performance, but the results have been vague ( 7 ). Some researchers found that development of an analytical approach using detailed checklists improved examiner reliability ( 8 , 9 ). However, other investigators reported no difference between glance and grade and checklist methods of assessment ( 10 ).…”
Section: Introductionmentioning
confidence: 99%